EXPLORING CULTURAL DIFFERENCES IN HEADLINE WRITING IN THE ENGLISH AND UZBEK PRESS - Mirzayeva Gulasal Ergashovna; Fayzullayeva Uldona Boybo’riyevna (TADQIQOTLAR, 2025)
Abstract. This article examines the stylistic elements present in the media language of English and Uzbek, concentrating on aspects such as brevity, figurative language, structural organization, and the balance between objectivity and engagement. The results indicate that English media prioritizes conciseness through succinct syntax and straightforward headlines, whereas Uzbek media leans towards a more formal tone with contextual depth, influenced by cultural norms. The practical results of this research advocate for improved journalism education, translation practices, and multilingual content strategies. Additionally, the social implications highlight how these stylistic variations affect public discourse, the accessibility of information, and trust levels within different linguistic and cultural settings, thus highlighting the need for targeted media literacy programs. The purpose of this study is to explore the cultural differences in advertising between Uzbek and the Great Britain. Two different samples of print magazine advertisements were taken from beauty magazines published in Uzbek and English to determine how much, if any, localization is occurring in Uzbek media.